RELATIONSHIP BETWEEN THE USE OF SOCIAL MEDIA AS A SOURCE OF PARENTING EDUCATION AND THE INCIDENCE OF POSTPARTUM BLUES IN THE WORKING AREA OF CIPAYUNG HEALTH CENTER, EAST JAKARTA - Deswani, Deswani; Bunga Untung, Andi Sari; Djuwitaningsih, Sri; Mulyanti, Yuli; Syafdewiyani, Syafdewiyani; Apriyani, Cherli Desi (Poltekkes Kemenkes Jakarta III, 2025)
The postpartum period is a critical phase for mothers, during which the emergence of postpartum blues can significantly affect emotional stability and maternal mental health. Alongside traditional information sources, social media has increasingly become a platform for parenting education. However, its role in influencing maternal psychological well-being remains unclear, particularly within community healthcare settings such as Puskesmas Cipayung in East Jakarta. Objective: This study aimed to examine the relationship between the use of social media as a source of parenting information and the incidence of postpartum blues among mothers attending the Cipayung Sub-district Health Center. Methods: A quantitative, cross-sectional design was employed involving 63 postpartum mothers selected through purposive sampling between March and May 2024. Data were collected using structured questionnaires assessing social media use for parenting information and postpartum blues symptoms. Statistical analysis was conducted using the Chi-square test to determine the association between variables. Results: The findings revealed a significant relationship between the use of social media as a parenting information source and the incidence of postpartum blues (p = 0.001, < 0.05). Mothers who frequently accessed social media for parenting guidance were more likely to experience mild to moderate postpartum blues. The study highlights that social media use for parenting information is significantly associated with the occurrence of postpartum blues. These results underscore the importance of integrating digital literacy and psychosocial support into nursing care to promote maternal mental well-being during the postpartum period.